THE RELATIONSHIP BETWEEN PARENTING STYLES AND SOCIAL COMPETENCE: A LITERATURE REVIEW - Abdul Kadir, Zahuren; Isa, Khairunesa (Jurnal 'Ulwan, 2025)
Parents have a vital impact on the lives of their children. During the period of childhood and adolescence, parents maintain a significant impact on the development of their children, moulding their principles, convictions, and actions. As children develop and progress, parents must adapt their parenting techniques to address their child's evolving requirements, offering suitable assistance and direction. The most recent report from the National Health and Morbidity Survey (2022) reveals that the largest occurrence of mental health issues is observed among those aged 16-19 years old who have difficulties related to peers, conduct, emotions, and hyperactivity. In the absence of adequate direction and parental accountability for moulding their children's character, they may encounter various challenges in their lives. This study seeks to comprehensively evaluate existing literature on the problem and develop a conceptual framework based on the findings of the literature review.